2004
DOI: 10.1063/1.1704613
|View full text |Cite
|
Sign up to set email alerts
|

Features of the local structure of fine-grained HTSC YBa2Cu2.985 57Fe0.015Oy

Abstract: Polycrystalline high-Tc superconductors (HTSCs) with the composition YBa2Cu2.985 57Fe0.015Oy (y≈6.92, Tc=91–91.5 K) with micron and submicron grain sizes are investigated by the method of gamma resonance (Mössbauer) spectroscopy at temperatures of 293, 91, and 78 K. A correlation is found between the changes of the intensities of the components of the Mössbauer spectra and the mean grain sizes 〈D〉. It is shown that the observed changes in the spectra are caused by an interplane redistribution of oxygen wherein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…It should be noted that the oxygen content in the O5 positions noticeably (by a factor of 2-3) exceeds the corre sponding values for macrocrystalline samples. This effect was also established earlier using Mössbauer spectroscopy data [4,5].…”
Section: Discussion Of Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…It should be noted that the oxygen content in the O5 positions noticeably (by a factor of 2-3) exceeds the corre sponding values for macrocrystalline samples. This effect was also established earlier using Mössbauer spectroscopy data [4,5].…”
Section: Discussion Of Resultssupporting
confidence: 82%
“…Thus, by varying the conditions D 〈 〉 of high temperature treatment, it is possible to control the degree of cation ordering in this system. Earlier magnetic, X ray, and Mössbauer studies [3][4][5][6][7] have shown that the properties of single phase YBa 2 Cu 3 O y fine crystalline HTSCs with an orthor hombic crystal structure (both in the superconducting and normal states) noticeably differ from the proper ties of macrocrystalline HTSCs of the same composi tion and with the same superconducting transition temperatures T c , but synthesized under conditions closer to equilibrium. It was found that for fine crys talline YBa 2 Cu 3 O y , the relations between the unit cell parameters, T c , and oxygen index y established earlier for equilibrium samples (see, for example, [8]) are not observed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations